Five-Factor Asset Pricing Model Fama and French dalam Memahami Excess Return Saham Syariah sebelum dan sesudah Diumumkan Covid-19 di Indonesia - Sunarsih, Sunarsih; Sholihati, Aziza Musyrifa (Universitas Muhammadiyah Surakarta, 2023)
This study aims to examine and analyze the effect of the Five Factor Asset Pricing Model Fama and French (risk premium, size, book-to-market ratio, profitability, and investment) on the excess return of Islamic stocks in Indonesia, as well as to test whether there is a difference between excess return before and after the announcement of Covid-19 in Indonesia. The sample in this study was taken from 279 companies listed on the Indonesian Sharia Stock Index (ISSI). The type of data used is time series daily. The research method used is multiple linear regression analysis. Based on the results of the study, it shows that the risk premium variable has a significant effect on the excess return of the Islamic stock portfolio registered at ISSI before and after the announcement of Covid-19 in Indonesia. Meanwhile, the variables of size, profitability, and investment have no effect on excess return, both before and after the announcement of Covid-19. Meanwhile, the book-to-market ratio has no effect on excess return before the announcement of Covid-19 and has a significant effect on excess return after the announcement of Covid-19.